Moderating Role of Remittance Inflows in Testing the Validity of Ecological Footprint-Induced Environmental Kuznets Curve (EKC) Hypothesis in Nigeria: An ARDL bound testing approach - Umar, Ahmed Tukur; Salihu, Bobbo (NIU Journal of Social Sciences; Vol 10 No 1 (2024): NIU Journal of Social Sciences, Vol. 10 No. 1, March 2024, 2024)
The paper tests the validity of ecological footprint induced-environmental Kuznets curve (EKC) hypothesis by considering the moderating role of remittance inflows in environmental quality -economic growth nexus in the context of Nigeria from 1980 to 2022. The study employed an ARDL bound testing approach, the results of both the short and long-run revealed that the coefficients of economic growth (GDP) and economic growth squared (GDP 2 ) is significantly positive and negative respectively.  This indicates an inverted U-shaped relationship between environmental degradations and economic growth thereby authenticating the validity of the EKC hypothesis in Nigeria. Furthermore, remittance inflows exert a negative and significant impact on environmental quality in the short-run but the coefficient is insignificant in the long-run. The interactive term of GDP and remittance inflows exert a positive and significant impact on environmental degradations in the short-run thereby revealing a complementary role by both the two variables in deteriorating the environment in the short-run, although the coefficient is insignificant in the long-run. The interactive between squared GDP and remittance inflows revealed a negative significant impact on environmental pollution thereby indicating a substitutability role by the two variables in improving the quality of the environment. Based on the findings, it is recommended that government should invests in research and development (R&D) on green energies and environmentally friendly technologies. personal remittances received should be channeled toward financing environmentally friendly businesses for environmental sustainability in Nigeria. Keywords: Ecological Footprint-Induced, Environmental Kuznets Curve, and Nigeria